1992
DOI: 10.1007/bf00968397
|View full text |Cite
|
Sign up to set email alerts
|

Enhanced GABA release in cerebral cortical slices derived from rats with thioacetamide-induced hepatic encephalopathy

Abstract: The release of newly loaded [3H]GABA was studied in slices of different brain regions derived from rats in which acute hepatic encephalopathy (HE) was induced with a hepatotoxin thioacetamide. HE increased both spontaneous and high (50 mM) ammonium chloride-evoked GABA release in cerebral cortical slices by 38% and 50%, respectively. No effects of HE were noted in cerebellar or striatal slices. An increased release of GABA in the cerebral cortex may contribute to the endogenous benzodiazepine-mediated enhancem… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
5
0

Year Published

1994
1994
2013
2013

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 30 publications
(6 citation statements)
references
References 13 publications
1
5
0
Order By: Relevance
“…Previous studies and our current data confirm that acute hepatic failure induced by TAA treatment can increase GABA [39] and glutamate levels [5] in the cerebral cortex. TAA induced an increase in both GABA (Figure S6A) and glutamate (Figure S6B) release compared with those of controls, causing a maximal 44% and 245% increase ( P <0.05), respectively.…”
Section: Resultssupporting
confidence: 89%
“…Previous studies and our current data confirm that acute hepatic failure induced by TAA treatment can increase GABA [39] and glutamate levels [5] in the cerebral cortex. TAA induced an increase in both GABA (Figure S6A) and glutamate (Figure S6B) release compared with those of controls, causing a maximal 44% and 245% increase ( P <0.05), respectively.…”
Section: Resultssupporting
confidence: 89%
“…Our data suggest that increased circulating (32, 33) and brain (33)(34)(35)(36) glutamine levels leading to increased concentrations and release of brain GABA may be involved in the hepatic encephalopathy of liver failure and ammonia toxicity (37). GABAergic transmission has been implicated in the pathogenesis of hepatic encephalopathy (38,39), and antagonists of GABA receptors can ameliorate manifestations of this disorder. Decreased glutamate levels have consistently been observed in brain homogenates from rats with acute liver failure (40) and from patients who died of hepatic coma (41).…”
Section: Discussionmentioning
confidence: 81%
“…GABAergic transmission has been implicated in the pathogenesis of hepatic encephalopathy (38,39), and antagonists of GABA receptors can ameliorate manifestations of this disorder. Decreased glutamate levels have consistently been observed in brain homogenates from rats with acute liver failure (40) and from patients who died of hepatic coma (41).…”
Section: Discussionmentioning
confidence: 99%
“…This rationale has been reproduced in various animal models of HE as well (Bassett et al, 1987;Gammal et al, 1990). Increased GABA'ergic tone in HE may be ascribed to increased levels of circulating natural benzodiazepines (Basile et al, 1991), increased synthesis of GABA A modulating neuroactive seroids (Ahboucha and Butterworth, 2007), increased availability of GABA and activation of GABA A receptors (Olasmaa et al, 1990;Wysmyk et al, 1992), while ammonia has also been found to increase GABA binding to the GABA A receptor (Ha and Basile, 1996). These events may also be attributed to an over zealous reaction to the potentially damaging levels of excitatory amino acids and elevated ammonia.…”
Section: The Neurochemistry Of Hepatic Encephalopathymentioning
confidence: 99%